Insights into the recognition of hypermucoviscous Klebsiella pneumoniae clinical isolates by innate immune lectins of the Siglec and galectin families - Campanero-Rhodes, María Asunción; Martí, Sara; Hernández-Ortiz, Noelia; Cubero, Meritxell; Ereño-Orbea, June; Ardá, Ana; Jiménez-Barbero, Jesús; Ardanuy, Carmen; Solís, Dolores (Frontiers in Immunology, 2024)
Klebsiella pneumoniae is an opportunistic bacterium that frequently colonizes the nasopharynx and gastrointestinal tract and can also cause severe infections when invading other tissues, particularly in immunocompromised individuals. Moreover, K. pneumoniae variants exhibiting a hypermucoviscous (HMV) phenotype are usually associated with hypervirulent strains that can produce invasive infections even in immunocompetent individuals. Major carbohydrate structures displayed on the K. pneumoniae surface are the polysaccharide capsule and the lipopolysaccharide, which presents an O-polysaccharide chain in its outermost part. Various capsular and O-chain structures have been described. Of note, production of a thick capsule is frequently observed in HMV variants. Here we examined the surface sugar epitopes of a collection of HMV and non-HMV K. pneumoniae clinical isolates and their recognition by several Siglecs and galectins, two lectin families of the innate immune system, using bacteria microarrays as main tool. No significant differences among isolates in sialic acid content or recognition by Siglecs were observed. In contrast, analysis of the binding of model lectins with diverse carbohydrate-binding specificities revealed striking differences in the recognition by galactose-and mannose-specific lectins, which correlated with the binding or lack of binding of galectins and pointed to the O-chain as the plausible ligand. Fluorescence microscopy and microarray binding studies of galectin-9 binding to entire cells and outer membranes of two representative HMV isolates supported the bacteria microarray results. In addition, Western blot analysis of the binding of galectin-9 to outer membranes unveiled protein bands recognized by this galectin, and fingerprint analysis of these bands identified several proteins containing potential O-glycosylation sites, thus broadening the spectrum of possible galectin ligands on the K. pneumoniae surface. Moreover, Siglecs and galectins apparently target different structures on K. pneumoniae surfaces, thereby behaving as non-redundant complementary tools of the innate immune system.